Postcolonial identities and West African literature - Das, Anwesha (Cambridge Scholars Publishing, 2023)
"Anchored in postcolonial theory, this book highlights the concept of "postcolonial soliloquies" as an original idea in analyzing West African literature. It uses the political theory of "dialogue" to broaden the reader's understanding of history, culture, identity and indigenous memories. The book shows how the novels of T. Obinkaram Echewa plunge into the known territory of colonial history with new boundaries." --